Jalur Distribusi dan Pembentukan harga Komoditas Cabe Merah di Purwokerto - Neni Widayaningsih; Rakhmat Priyono (EKO-REGIONAL, 2012)
Characteristic of price inflation in Indonesia was dominated generally by cost push inflation than demand pull inflation. It was caused by the relevancy of agents that involved in the commodities distribution chain that impacted to the price of supply side. The high price will lead the inflation generally. The length of distribution chain will influence also to the high level of inflation rate. Related to the distribution chain that impact to commodity inflation, this research try to identify how the form of the distribution chain to chili commodity in Purwokerto and to detect the rule of each agents that involvement. It was find out that first, distribution chain of chili commodity could consist of two types; (1) farmer – broker – grocer – retailer – consumer; and (2) farmer – retailer – consumers. The first type dominated more in chili market. Second, the analyses showed that the change of price structure in chili market was influenced more by the transaction of grocer and retailers side. It indicated that the fluctuation of chili price was not pushed by final market requirement, but rather of how the interaction among seller conducted. Keywords: cost push inflation, distribution chain, chili commodity